Pengaruh Corporate Social Responsibility dan Kepercayaan Merek terhadap Loyalitas Merek Bank Nagari Capem UNP pada Mahasiswa UNP - Evanita, Susi; Thabrani, Gesit; Chairil, Arsala Bilhuda (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2016)
This research aims to analyze the effect of (1) corporate social responsibility,and (2) brand trust towards brand loyalty UNP branch Nagari Bank on Padang State University Student. This research belongs to a causative research. The population in this research is the student of Padang State Universitywho ever had dealings in Nagari Bank and knowing CSR program of Nagari Bank. The sampling technique used was accidental sampling, total sample with as many as 100 samples. Methods of analysis used is the regression. The results of this research indicate that: (1) corporate social responsibility affect significantly to brand loyalty Nagari Bank on Padang State University Student and (2) brand trust affect significantly toward brand loyalty Nagari Bank on Padang State University student.